PENGARUH STRUKTUR MODAL, PROFITABILITAS, DAN LIKUIDITAS TERHADAP PERINGKAT OBLIGASI PADA PERUSAHAAN YANG MENERBITKAN OBLIGASI DI BURSA EFEK INDONESIA - Yan Hartono (2013)
his study aimed to examine the effect of capital structure, profitability, and liquidity Against bond ratings on companies that issue bonds in Indonesia Stock Exchange. The population number of 125 companies listed on the Indonesia Stock Exchange and has a bond rating of PT. Pefindo in 2012. Data obtained from financial statements that have been published in 2011. The sample used in this study were 34 companies that include the category Non-Financial Companies. The analysis technique used is multiple linear regression and hypothesis testing using t-statistics and F-statistics with a confidence level of 5%. These results indicate that the positive effect on the liquidity and Profitability of bond ratings, while the other variables in this research that the capital structure negatively affect bond ratings. We advise to investors in the Indonesia Stock Exchange in order to observe to other factors that affect bond ratings in making their investment decisions.